2006
DOI: 10.1123/ijsnem.16.2.214
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sports Nutrition Knowledge of New Zealand Premier Club Rugby Coaches

Abstract: Little is known about if and how team coaches disseminate nutrition information to athletes. In a census survey, New Zealand premier rugby coaches (n = 168) completed a psychometrically validated questionnaire, received by either Internet or standard mail (response rate, 46%), identifying their nutrition advice dissemination practices to players, their level of nutrition knowledge, and the factors determining this level of knowledge. The majority of coaches provided advice to their players (83.8%). Coaches res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
68
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 13 publications
8
68
0
1
Order By: Relevance
“…These conclusions are comparable with those of another research group (4,9), and show that coaches are misled about weight control issues due to the spread of numerous nutritional myths and misinformation in our societies.…”
Section: Weight Controlsupporting
confidence: 79%
See 3 more Smart Citations
“…These conclusions are comparable with those of another research group (4,9), and show that coaches are misled about weight control issues due to the spread of numerous nutritional myths and misinformation in our societies.…”
Section: Weight Controlsupporting
confidence: 79%
“…Rosenbloom, Jonnalagadda, and Skinner (6) reported that athletes had a faulty perception of the roles of carbohydrates, proteins, vitamins, and minerals. Many other studies have also noted these results (7,8) showed that approximately 84% of trainers advised their athletes (9). Torres-McGehee et al (5) unveiled that 43% of athletes sought nutrition advice from their trainer.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Athletes also obtain information from a variety of other sources including school or tertiary-education programs, books, sport-specific magazines, the mass media, and, increasingly, the Internet (Burns, Schiller, Merrick, & Wolf, 2004;Jacobson, Sobonya, & Ransone, 2001;Parr, Porter, & Hodgson, 1984). Even at the elite level, nutritioneducation programs for athletes may be predominantly coach driven and reactive, with depth and frequency of intervention influenced by financial constraints (Zinn, Schofield, & Wall, 2006). In contrast to education programs in other areas of nutrition, evaluation of athlete nutrition-education programs is rarely reported (Abood, Black, & Birnbaum, 2004;Collison, Kuczmarski, & Vickery, 1996).…”
mentioning
confidence: 99%